Translation, cross-cultural adaptation and psychometric evaluation of yoruba version of the short-form 12 health survey - Mbada, C. E.; Awokoya, A. S.; Oyewole, O. O.; Idowu, O. A.; Akinsulore, A.; Fatoye, C.; Oke, K. I.; Fatoye, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Short Form 12 (SF-12) health survey has found its utility in clinical and research settings because of its short length that spares time. Though several translations into other languages do exist there is none available in Yoruba language. Hence, this study’s objective was to culturally adapt and determine the reliability and validity of the Yoruba translated version of the SF-12.Methods. Forward and backward translations of SF-12 into Yoruba version of SF-12 (Y-SF-12) were done using the International Quality of Life Assessment Project Guidelines. Healthy participants were assessed using both English and Yoruba versions of SF-12 for the validation phase, and two weeks later were reassessed with the Y-SF-12 for the reliability phase. Results. Participants were 225 males and 171 females. The mean scores for each scale range from 73.4 to 86.1, with no gender difference. All scale and domain scores evidenced a negative skew and ranges from -1.79 to -0.62. Concurrent validity (0.879 – 0.938) and convergent validity (0.786 – 0.907) appeared to be good as reflected by their correlation values. The internal consistency of Y-SF-12 was good as Cronbach’s Alpha ranged between 0.899 and 0.968, while the Intraclass Correlation Coefficient (ICC) ranged between 0.775 and 0.949. Conclusion. This is the first study to assess the psychometric properties of the Y-SF-12. It appears to be valid and may be an appropriate tool for assessing health-related quality of life among Yoruba population. The tool may help to improve the health outcomes of individuals, and redress health inequalities in low and middle-income countries.